Pengaruh BI Rate, Inflasi, dan Kurs Terhadap Nilai Aktiva Bersih Reksadana Syariah Campuran - Mohammad Apriyanto; Diharpi Herli Setyowati; Ine Mayasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The development of the Islamic finance industry in Indonesia has experienced a rapid increase, one of which is investment activities that occur in the capital market. Islamic mutual funds are an alternative for the public in investing. Mixed Sharia Mutual Funds are a form of product from sharia mutual funds that have less risk than other types of sharia mutual funds. The measuring instrument in sharia mutual fund investment is Net Asset Value (NAV). Things that can affect,the NAV of a sharia mutual,fund are the BI rate, Inflation, and the Exchange Rate. This study aims to determine the impact of these three variables on the NAV of Islamic mutual funds. Sources of data in the form of secondary data with purposive sampling method. This research uses multiplier,linear regression analys method. The results of this study indicate that the BI Rate and Inflation variables have’s a partially significant effect on the NAV of mixed sharia mutual fund, but the exchange rate variable has no partial significant effect on the NAV of mixed sharia mutual fund. The results also show that the BI Rate, Inflation and Exchange Rate have a simultaneous effect on the NAV of Islamic mutual funds.